Pengaruh Karakteristik Perusahaan, Sales Growth Dan Managerial Ownership Terhadap Tax Avoidance - Bani Haniyyah Ramadhan; Suripto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research aims to prove empirically the effect of company characteristics as proxied by leverage, profitability, company size and sales growth and managerial ownership on tax avoidance in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2016-2020. The research method used is quantitative associative. The type of data used is secondary data. Sampling using purposive sampling technique. The number of research samples was 16 companies with a research period of 5 (five) years, in order to obtain 80 observational data. data analysis with panel data regression analysis. The results showed that profitability had a negative effect on tax avoidance, while firm size had a positive effect on tax avoidance, but leverage, sales growth, and managerial ownership had no effect on tax avoidance. The results show that leverage, profitability, firm size, sales growth, and managerial ownership simultaneously affect tax avoidance